Challenges faced by the patients in the management of risk factors of non-communicable diseases in a government primary health care setting of Puducherry - Solaimalaichami, Jayaramachandran; Anbalagan, Surekha; Anbalagan, Suguna; Narayanan, Seetharaman; Pownraj, Dhivya (International Journal Of Community Medicine And Public Health, 2019)
Background: India’s current approach for intervention in non-communicable diseases (NCDs) is more in terms of early diagnosis and treatment. The focus should also be on the management of risk factors in the diseased individuals. The objectives of the study are to measure the risk factors of NCDs, lifestyle modification followed by them and to assess the challenges in reducing the risk factors of NCDs faced by the study population. Methods: The study was conducted between March and June 2017 in 2 government primary health centres (PHCs) in Puducherry. Based on systematic random sampling, 200 patients enrolled in NCD clinic with diabetes mellitus, hypertension, Stroke and myocardial infarction were selected for the study. After obtaining written informed consent, data was collected. Results: Out of 200 participants, majority of them were in the age group of 51-70 years (60%), females (71%) and living in nuclear family (83%). Among 200 participants, 23.5% of them had diabetes mellitus, 42% had hypertension and 24% had diabetes with hypertension. The risk factors that many of the participants had were excessive salt and sugar intake, overweight and obesity, less vegetable and fruits intake and alcohol consumption. Out of 200 participants, the major challenges in reducing the salt and sugar intake were lack of awareness and no family support. Conclusions: Most of the participants were oldest females who had diabetes or hypertension. The most common NCD they were suffering from were diabetes and hypertension. The major challenge in the management of NCDs is lack of awareness.